World trigger - Ashihara, Daisuke; Olsen, Lillian
Destroy thy Neighbor! A gate to another dimension has burst open, and invincible monsters called Neighbors invade Earth. Osamu Mikumo may not be the best among the elite warriors who co-opt other-dimensional technology to fight back, but along with his Neighbor friend Yuma, he'll do whatever it takes to defend life on Earth as we know it.
"First published in Japan in 2013 by Shueisha Inc., Tokyo"--Title page verso. Reads from right to left.
Keywords: Aliens -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Graphic novels